2020
DOI: 10.1177/0363546520905884
|View full text |Cite
|
Sign up to set email alerts
|

Adjunct Analgesia Reduces Pain and Opioid Consumption After Hip Arthroscopy: A Systematic Review of Randomized Controlled Trials

Abstract: Background: Patients who undergo hip arthroscopy inevitably experience pain postoperatively; however, the efficacy and safety of adjunct analgesia to prevent or reduce pain are not well-understood. Purpose: To perform a comprehensive qualitative synthesis of available randomized controlled trials evaluating the effect of adjunct analgesia on postoperative (1) pain, (2) opioid use, and (3) length of stay (LOS) in patients undergoing hip arthroscopy. Study Design: Systematic review. Methods: PubMed, OVID/MEDLINE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 45 publications
0
24
0
Order By: Relevance
“…A systematic review and network meta-analysis of 14 level I evidence studies suggested that adjunct anesthesia (local anesthesia infiltration) significantly reduces postoperative pain and opioid consumption. 23 Although perioperative regional blockade may reduce pain after hip arthroscopy, there is a significant increase in fall risk. 24 Although not previously discretely analyzed and reported, patient education is likely a critical component of postoperative pain and expectation management.…”
Section: See Related Article On Page 1599mentioning
confidence: 99%
“…A systematic review and network meta-analysis of 14 level I evidence studies suggested that adjunct anesthesia (local anesthesia infiltration) significantly reduces postoperative pain and opioid consumption. 23 Although perioperative regional blockade may reduce pain after hip arthroscopy, there is a significant increase in fall risk. 24 Although not previously discretely analyzed and reported, patient education is likely a critical component of postoperative pain and expectation management.…”
Section: See Related Article On Page 1599mentioning
confidence: 99%
“…The opioid epidemic in the United States is a well-recognized issue [ 29 ] and the potential risks of opioid use, in addition to the associated health care costs, should encourage surgeons to seek alternatives to postoperative pain management. The efficacy of non-opioid medications in this setting has been demonstrated in several studies [ 3 , 30 , 31 ] and the American Society of Anesthesiologists (ASA) and the American Pain Society (APS) emphatically recommend the use of non-opioid analgesia in the post-operative period, barring contraindications [ 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…As it is largely performed in an outpatient setting [ 1 , 2 ], hip arthroscopy requires proper post-operative pain management. Adequate post-operative pain control is of utmost importance as it increases patient satisfaction, decreases opioid consumption and allows early ambulation and rehabilitation [ 3–5 ]. Moreover, inadequate post-operative pain control may lead to adverse physiologic effects, delayed recovery and increased risk of developing chronic pain associated with the procedure [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One manner by which surgeons have attempted to lessen perioperative pain is with the use of various adjunct analgesic modalities such as nerve blocks, intraoperative intra-articular or extracapsular anesthetic injections, and nonsteroidal anti-inflammatory drugs. 23 Regional nerve blocks have been accepted as a standard pain management practice for patients undergoing shoulder arthroscopy 33,34 and anterior cruciate ligament reconstruction. 12,29 However, the use of nerve blocks as a method of perioperative pain control for patients undergoing hip arthroscopy is more novel and may include a fascia iliaca block (FIB), 2,15,18 lumbar plexus block (LPB), 2,19 quadratus lumborum block, 20,26 or sciatic nerve block.…”
mentioning
confidence: 99%